Survivors of Ebola Virus Disease Develop Polyfunctional Antibody Responses. (12th July 2019) - Gunn, Bronwyn M; Roy, Vicky; Karim, Marcus M; Hartnett, Jessica N; Suscovich, Todd J; Goba, Augustine; Momoh, Mambu; Sandi, John Demby; Kanneh, Lansana; Andersen, Kristian G; Shaffer, Jeffrey G; Schieffelin, John S; et al.
Abstract: Monoclonal antibodies can mediate protection against Ebola virus (EBOV) infection through direct neutralization as well as through the recruitment of innate immune effector functions. However, the antibody functional response following survival of acute EBOV disease has not been well characterized. In this study, serum antibodies from Ebola virus disease (EVD) survivors from Sierra Leone were profiled to capture variation in overall subclass/isotype abundance, neutralizing activity, and innate immune effector functions. Antibodies from EVD survivors exhibited robust innate immune effector functions, mediated primarily by IgG1 and IgA1. In conclusion, development of functional antibodies follows survival of acute EVD. Abstract : The humoral immune response in human survivors of Ebola virus disease includes the development of neutralizing antibodies and polyfunctional IgG1 and IgA antibodies that can mediate effector functions against the Ebola virus glycoprotein via multiple innate immune effector cell types.